The Tubulin Inhibitor VERU-111 in Combination With Vemurafenib Provides an Effective Treatment of Vemurafenib-Resistant A375 Melanoma - Hongmei Cui; Hongmei Cui; Qinghui Wang; Duane D. Miller; Wei Li (Frontiers Media S.A., 2021)
Melanoma is one of the deadliest skin cancers having a five-year survival rate around 15-20%. An overactivated MAPK/AKT pathway is well-established in BRAF mutant melanoma. Vemurafenib (Vem) was the first FDA-approved BRAF inhibitor and gained great clinical success in treating late-stage melanoma. However, most patients develop acquired resistance to Vem within 6-9 months. Therefore, developing a new treatment strategy to overcome Vem-resistance is highly significant. Our previous study reported that the combination of a tubulin inhibitor ABI-274 with Vem showed a significant synergistic effect to sensitize Vem-resistant melanoma both in vitro and in vivo. In the present study, we unveiled that VERU-111, an orally bioavailable inhibitor of α and β tubulin that is under clinical development, is highly potent against Vem-resistant melanoma cells. The combination of Vem and VERU-111 resulted in a dramatically enhanced inhibitory effect on cancer cells in vitro and Vem-resistant melanoma tumor growth in vivo compared with single-agent treatment. Further molecular signaling analyses demonstrated that in addition to ERK/AKT pathway, Skp2 E3 ligase also plays a critical role in Vem-resistant mechanisms. Knockout of Skp2 diminished oncogene AKT expression and contributed to the synergistic inhibitory effect of Vem and VERU-111. Our results indicate a treatment combination of VERU-111 and Vem holds a great promise to overcome Vem-resistance for melanoma patients harboring BRAF (V600E) mutation.